THE INFLUENCE OF USER EXPERIENCE AND USER INTERFACE ON CUSTOMER LOYALTY THROUGH CINEMA CUSTOMER SATISFACTION THAT USED TIX ID APPLICATION IN MEDAN CITY - Youanita Tri Sevanya Damanik; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Online applications are now growing, for example in online ticket sales transactions (e-ticketing). Entrepreneurs start developing online ticket sales business ideas (e-ticketing) not only in the sale of lodging tickets, aircraft, trains, or other transportation, but also to expand to the world of film, namely online cinema ticket sales like TIX ID. This study aims to find out and analyze the effect of User Experience and User Interface on customer loyalty through cinema customer satisfaction that uses the TIX ID application. This research is associative research and the type of data used is quantitative data. The population in this study are cinema customers who use the TIX ID application in Medan, which is unknown. The number of samples in this study was 135 respondents. Sampling techniques using purposive sampling with criteria have a TIX ID application and have used the TIX ID service for at least 2 times and are in the city of Medan. The data analysis used is structural equation modeling. The results of this study indicate that the User Experience and User Interface, directly have a positive and significant effect on the satisfaction and loyalty of cinema customers who use TIX ID. Indirectly, User Experience and User Interface have a positive and significant effect on loyalty through the satisfaction of cinema customers who use TIX ID.